(untitled) (Italian Journal of Public Health, 2008)
Background: The Disability Information System Project started in 2000 following an agreement between the current Ministry of Social Solidarity and Istat in implementation of article 41-bis of Law 162/98, that highlighted the need to promote statistical and cognitive surveys on disability. Methods: The System was created to meet the increasing attention of policy makers and society in general to people with disabilities and their participation in society. The system provides statistical information on disability by integrating and coordinating data sources available relating to this issue in Italy and to establish new sources that are suitable for addressing the current information gaps. Discussion: Activities of Istat in recent years have reached the ambitious goal of transforming the extensive data and numerous documents of an administrative nature on disability into statistical information. It means to create an organised body of information, documented and processed using statistical tools that can be understood and used by policy-makers, experts, and citizens. Conclusions: The phenomena analysed are very often characterised by various dimensions that are unlikely to be independent of one another. It is precisely in studying these phenomena that the information system provides significant added value since it makes it possible to have quicker and a guided access to the multiplicity of data sources that describe different aspects of a topic. This makes possible for the user to integrate information and to create an overall or sufficiently comprehensive picture.